O sabor açaí da dança breaking - NASCIMENTO, Layse Ranielle da Silva (2018)
A brief "tasting" about the taste of breaking dance. A question about the meaning of flavor for those who dance and how you can influence with regard to one or b.boy b.girl. Dialogue with Fleury (2007), dance and laser to work as street dancers. Alves and Dias (2004), bodies and senses in hip hop. Duarte Junior (2000), the taste of knowledge through dance. Gariba (2007), dance and education.